2019
DOI: 10.3390/photonics6010034
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of 4 × 4 Mueller Matrix Transformation Parameters for Biomedical Imaging

Abstract: Mueller matrix polarimetry is a potentially powerful technique for obtaining microstructural information of biomedical specimens. Thus, it has found increasing application in both backscattering imaging of bulk tissue samples and transmission microscopic imaging of thin tissue slices. Recently, we proposed a technique to transform the 4 × 4 Mueller matrix elements into a group of parameters, which have explicit associations with specific microstructural features of samples. In this paper, we thoroughly analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…From Figure we can see that the structural features revealed by the MMT parameters t 3 and x 3 are very similar to those revealed by the MMPD parameters δ and θ . Our recent studies have demonstrated that the MMT parameters can be calculated more easily and quickly, while the MMPD retardance parameters have slightly better correlations with tissue birefringence for transmission imaging . Since the computational time consuming is not the primary consideration here, in the following sections we will choose the MMPD parameters δ and θ for further studies.…”
Section: Resultsmentioning
confidence: 99%
“…From Figure we can see that the structural features revealed by the MMT parameters t 3 and x 3 are very similar to those revealed by the MMPD parameters δ and θ . Our recent studies have demonstrated that the MMT parameters can be calculated more easily and quickly, while the MMPD retardance parameters have slightly better correlations with tissue birefringence for transmission imaging . Since the computational time consuming is not the primary consideration here, in the following sections we will choose the MMPD parameters δ and θ for further studies.…”
Section: Resultsmentioning
confidence: 99%
“…[26][27][28][29] Therefore, MMIP is becoming increasingly attractive for distinguishing the structural features of biological tissue in food quality control and medical diagnostics. 18,24,28,[30][31][32][33][34][35][36][37] Optical characterization of biological tissue within the framework of the Stokes-Mueller formalism is based on measuring the bulk tissue's polarimetric transfer function, known as its Mueller matrix. This information-rich tissue signature includes the full polarization information reflecting its biophysical properties.…”
Section: Mueller Matrix Polarimetrymentioning
confidence: 99%
“…Different decomposition techniques have been developed to extract the information on polarization properties of the sample encoded in all 16 elements of the MM, e. g. Mueller matrix polar decomposition (MMPD) 45 and the Mueller matrix transformation (MMT). 32,46 Here, we applied Lu-Chipman decomposition 45 which shows any physically realizable MM 47 can be decomposed into a product of three MMs of the basic optical components including diattenuator (D), followed by retarder (R), and depolarizer (Δ). 45 Biological tissues are highly scattering media composed of cells, protein fibers, and optically active molecules, so they are expected to possess such polarimetric properties as depolarization, linear birefringence, and optical activity.…”
Section: Mueller Matrix Polarimetrymentioning
confidence: 99%
“…Polarization imaging technique is a promising noninvasive method to provide rich microstructural information about different types of the sample ( KU et al, 2019 ; Ramella-Roman et al, 2020 ), primarily used as biomedical imaging applications ( Xiao et al, 2019 ). It has been combined with microscopy ( He et al, 2019 ) and endoscopy to help achieve precision and noninvasive medical detection and treatment, and polarization parameters have been proposed to explain distinctive pathological structures ( Lu and Chipman, 1996 ; He et al, 2019 ) and help to detect human skin, esophageal, colorectal, and oral cancers and cervical carcinoma ( Sheng et al, 2019 ) among others. Among the available polarization techniques, Mueller matrix imaging can provide comprehensive descriptions on the optical properties of biological samples ( Pezzaniti and Chipman, 1995 ; Chung et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%